Dialectics of the theological and the speculative - Bevzuk, Natalia (Sententiae, 2011)
The article considers the problem of theology and the speculative in their dialectic and systemic sense. The author comes to the conclusion that the more spontaneously the necessity of historical theology is grounded (in a narrow sense, as exegesis, as church and dogmatic history), the more inevitable becomes their need of abstraction and speculative comprehension of themselves. On the other hand, this very speculative comprehension of oneself allows theology to develop fruitfully and systemically. The author considers this dialectic connection on the example of Protestant theology.